1983
DOI: 10.1007/bf00542525
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in effects on blood pressure, flicker fusion frequency, salivation and pharmacokinetics of single oral doses of dothiepin and amitriptyline

Abstract: Blood pressure, critical flicker fusion frequency (CFF), salivary flow rate and pharmacokinetics were compared in 7 young healthy volunteers (average age: 22.7 years) and in 7 elderly healthy volunteers (average age: 70.6 years) after single oral doses of the antidepressants dothiepin (DP) 25 mg and amitriptyline (AMP) 25 mg. Systolic blood pressure fell further and the reduction lasted longer in the elderly than in the young after both drugs. The decrease in CFF after AMP 25 mg, and the reduction in salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In a pre vious study [ 15], we reported that absence of subjective symptoms, despite evidence of obvious abnormalities from ophtalmological examination, was observed more frequently in neuropsychiatric patients than tuberculosis patients as controls, and especially in schizophrenic pa tients with highly advanced emotional disorders [15], Emotional disorders, which may be present in the elderly as well as in neuropsychiatric patients, are likely to be discrepant between subjective rating and objective mea surement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pre vious study [ 15], we reported that absence of subjective symptoms, despite evidence of obvious abnormalities from ophtalmological examination, was observed more frequently in neuropsychiatric patients than tuberculosis patients as controls, and especially in schizophrenic pa tients with highly advanced emotional disorders [15], Emotional disorders, which may be present in the elderly as well as in neuropsychiatric patients, are likely to be discrepant between subjective rating and objective mea surement.…”
Section: Discussionmentioning
confidence: 99%
“…Fur thermore, the incidence and severity of these reactions are recognized to be greater in elderly patients who are prone to be more depressed than others [2,9], The adverse reactions become troublesome, and occasionally even harmful to the elderly patient [2,9], Although sub jective evaluation of these reactions is apt to be in fluenced by psychological conditions [15], especially in psychiatric and/or elderly patients who are often treated with antidepressants, self-rating has been used almost exclusively except in some experimental studies. Accu rate information about adverse drug reactions and phar macological effects in humans would insure greater safety of drug therapy and better understanding of pharmacody namics of these drugs, but this information appears to be severely lacking.…”
mentioning
confidence: 99%
“…32,33 On the other hand, in vivo studies showed equivocal results (a decrease or no change) in hepatic drug clearance by different CYP isoforms in the elderly, as shown in Table 2. [17][18][19]28,29,[34][35][36][37][38][39][40][41][42][43][44][45][46] The paradoxical pattern of in vitro versus in vivo activity of CYP enzymes in the elderly for phase I drug metabolism may be explained by the oxygen delivery theory: oxygen delivery to liver microsomes is not constrained in the in vitro studies, whereas in the in vivo studies, age-related alterations in the hepatic architecture (such as thickening and defenestration of hepatic sinusoidal endothelium and deposition of collagen) may reduce oxygen availability for phase I drug metabolism. 13,29,47 On the contrary, the enzyme system responsible for metabolism of drugs by conjugation [eg, glucuronidation, sulphation, and acetylation (phase II reaction)] requires oxygen indirectly to produce energy.…”
Section: Drug Distribution In Agingmentioning
confidence: 99%
“…Advanced-age-related changes in clearance of some drugs that undergo phase I metabolism by CYP isoforms in humans [21][22][23]34,35,[40][41][42][43][44][45][46][47][48][49][50][51][52]. …”
mentioning
confidence: 99%
“…The halflives of DP and AMP were longer, and the peak plasma levels of the two drugs were also higher in the elderly group than in the young group [5]. These age differences may be one of the factors which are related to the different effects on the systolic blood pressure.…”
Section: Discussionmentioning
confidence: 92%